A primary approach for separation and characterization of Î±-amylase from white pitaya (Hylocereus undatus) peels by polymer/salt two phase system - Shad, Zahra; Meor Hussin, Anis Shobirin; Akbari-adergani, Behrouz (Faculty of Biotechnology and Food Sciences, 2022)
Î±-Amylase was isolated from white pitaya peel with two phase system in aqueous media and then characterized. The effects of polyethylene glycol (PEG), PEG concentration, molecular weight, sodium citrate, and sodium chloride (NaCl) on yield and purification factor were studied. The highest purification factor (4.5) and yield (83%) were obtained in system PEG 6000 (14% w/w)-sodium citrate (18% w/w) with 6% (w/w) NaCl. The purified Î±-amylase molecular weight exhibited a band above 40 KDa by SDS-PAGE. Î±-Amylase showed optimum activity at pH of 6.0 and temperature of 55 Â°C. The activity of this enzyme was stable in the pH scope of 6-8 and temperature scope of 10-55 Â°C. Various metal ions were evaluated for amylase activation/inhibition effect. Na+ and Ca2+ were exhibited to have appropriate activating effect, where as Mn2+, Zn2+, Fe3+, Ni+, Ba+ and Cu2+ had inhibition effect. In addition, this enzyme showed remarkable stability in the existence of TritonX-100, SDS, sodium perborate, Tween 20 and Tween-80. In conclusion, this enzyme has high stability and activity at suitable temperature and pH, and in the existence of different surfactants and metal ions. This approach has a potential in progress of various industrial applications by introducing a method for applying new, low-cost, and biocompatible amylases source.